An Electrophilic Reagent for the Direct Introduction of the SCF2PO(OEt)2 Group to Molecules. (26th September 2016) - Xiong, Heng‐Ying; Bayle, Alexandre; Pannecoucke, Xavier; Besset, Tatiana
Abstract: An unprecedented electrophilic difluoromethylthiolating reagent (MesNHSCF2 PO(OEt)2 ) was designed. Under mild and metal‐free conditions, this new reagent reacted with various nucleophiles, thus offering an efficient and operationally simple tool for the construction of C−SCF2 PO(OR)2, N−SCF2 PO(OR)2, and S−SCF2 PO(OR)2 bonds. Finally, thanks to this new methodology, the synthesis of the non‐stereoidal anti‐inflammatory diflumidone was achieved.